Analisis Risiko Pembiayaan pada Produk Cicil Emas di BSI KFF Jember Politeknik Negeri - Rofiah, Zulfatur; Amarwati, Amara; Setianingrum, Nurul (Lembaga Yasin AlSys, 2026)
The Cicil Emas product is one of the investment financing products offered by Bank Syariah Indonesia (BSI) and is popular among the public because it facilitates gold ownership through an installment mechanism in accordance with sharia principles. However, the increasing public interest in this product is also accompanied by various risks that need to be managed effectively so that financing quality can be maintained. This study aims to analyze financing risks in the Cicil Emas product and the implementation of risk management carried out by BSI KFF Jember Politeknik Negeri in managing these risks. This study used a qualitative method with a descriptive approach. Data were obtained through observation, interviews, and documentation, with primary data sources from the bank and secondary data from books, journals, company documents, and other supporting sources. Data were analyzed using the interactive model of Miles and Huberman, which includes data collection, data reduction, data display, and conclusion drawing. The results show that the main risks in the Cicil Emas product include financing risk, market risk, and operational risk. To manage these risks, BSI KFF Jember Politeknik Negeri implements risk management through the stages of risk identification, measurement, monitoring, and control in accordance with applicable regulations. Risk management implementation is carried out through 5C analysis, periodic financing monitoring, determination of the Loan to Value (LTV) ratio, customer education, and improvement of human resource competence. The conclusion of the study affirms that the implementation of risk management in the Cicil Emas product plays an important role in maintaining financing quality and minimizing potential risks that may affect financing performance. The implications of this study provide practical contributions for Islamic banking institutions in strengthening investment financing risk governance based on murabahah in a more measurable, prudent, and sustainable manner.